Strategic University Management in the Context of Digitalization: The Experience of the World’s Leading Universities - Wadim Strielkowski; Elena N. Korneeva; Anna A. Sherstobitova; Alexandr Yu. Platitzyn (Интеграция образования, 2022)
Introduction. The research paper’s aim is to study the ongoing digitalization in all spheres of economy, which inevitably impacted on the strategic university management. It explains how universities and higher educational institutions strategically positioned themselves and searched for the novel pathways for innovation and development, which was further reinforced by the COVID-19 pandemic and the digital surge it brought. Materials and Methods. The authors analyzed the strategic university management in the context of digitalization using the literature review and their own analysis. They focus on the experience of the world’s best universities for inspiring the institutions of higher education in other countries and regions, helping them to improve information and communication technologies and digital skills. Results. Our results corroborate the ongoing digitalization in all spheres of economy and social life which was pushed further by the COVID-19 pandemic contributed to the transformation of the higher educational institutions challenging them to embark upon the path of in-depth transition, restructuring, and re-thinking their role and their mission with regard to the new challenges and novel technologies that are available on the market Discussion and Conclusion. The outcomes present interesting possibilities for their application in practice for some countries, most notably Russia. They can be of a special interest not only for the government officials responsible for fostering higher education and devising guidelines for the strategic management of universities and higher educational institutions, but also for the academic environment with its researchers and lecturers who seek to innovate based on the most recent and advanced trends in higher education (e.g. ministries and national authorities responsible for science, research, and education in different countries, such as the Ministry of Science and Higher Education, Ministry of National Education, Ministry for Research, as well as National Educational Authority or the World Bank, just to name a few).